Chatgpt Review: A Sophisticated Chatbot Models In Medical & Health-related Teaching And Learning - Nur Izah Ab Razak; Rahmita Wirza O.K. Rahmat; Muhammad Fawwaz Muhammad Yusoff (UPM Press, 2024)
Indexed by Scopus/MyCite